Feminism in literature a Gale critical companion - Bomarito, Jessica 1975-.; Hunter, Jeffrey W. 1966-.; Gale Group (Detroit Thomson Gale, 2005)
This six-volume set explores the history of women and feminism throughout literature, from classical antiquity to modern times. Topics covered include misogyny and women's social roles in ancient civilizations, 16th-century women's devotional literature, 17th- and 18th-century women's captivity narratives, the women's suffrage movement in 19th-century America, women writers of the "Lost Generation," lesbian literature, and much more.
v. 1. Antiquity-18th century, topics & authors -- v. 2. 19th century, topics & authors (A-B) -- v. 3. 19th century, topics & authors (C-Z) -- v. 4. 20th century, topics -- v. 5. 20th century, authors (A-G) -- v. 6. 20th century, authors (H-Z).
Electronic reproduction.
Keywords: Literature -- Women authors -- History and criticism; Women authors -- Biography; Women -- History; Electronic books